Ефективність методики вдосконалення силових здібностей боксерів із використанням вправ легкої атлетики - Фоменко, Вікторія Вікторівна; Хмелюк, О. В.; Колоколов, В. О.; Жогло, В. М.; Єфременко, А. М.; Крайник, Я. Б. (Національний педагогічний університет ім. М. П. Драгоманова, 2023)
Мета – обґрунтування ефективності методики комплексного розвитку силових здібностей боксерів 17-19 років. Учасники: боксери 18,05±1,50 років (n = 16), які були поділені на контрольну (КГ; n = 8) та експериментальну (ЕГ; n = 8) групи. Методи: аналіз даних науково-методичної літератури; педагогічне спостереження, тестування та експеримент; методи математичної статистики. Результати та їх обговорення. Особливість експериментальної методики полягала у поєднаному використанні специфічних та легкоатлетичних засобів у силовому тренуванні боксерів протягом 12 тижнів. Встановлено, що порівняно з традиційним підходом експериментальна методика сприяла позитивній динаміці показників сили м'язів рук та плечового поясу, силовій витривалості, а також швидкісно-силових якостей випробуваних. Висновки. Комплексний розвиток силових здібностей дозволяє оптимізувати процес розвитку сили боксерів 17-19 років у підготовчому періоді річного макроциклу.

Aim – substantiate the effectiveness of the method of comprehensive development of strength abilities of boxers aged 17-19. Objects: qualified men boxers aged 18.05±1.50 (n=16), who were divided into control (CG; n=8) and experimental (EG; n=8) groups. Methods: data analysis of scientific and methodical literature; pedagogical observation, verification and experiment; methods of mathematical statistics. Research results and discussion. Based on the analysis of the data of modern science and practice in the field of strength training of boxers, a comprehensive methodology for strength training of boxers aged 17-19 years in the preparatory period of the annual macrocycle was developed and tested. Its feature was the combined use of specific and non-specific means of strength training for boxers, which were grouped according to the block principle and implemented within 12 weeks. It was established that, compared to the traditional approach to improving the strength of qualified boxers, the experimental technique effectively and comprehensively influenced the dynamics of the strength indicators of the muscles of the arms and shoulder girdle, strength endurance, as well as the speed and strength qualities of the test subjects. Therefore, in the process of forming sports preparedness, which continues from cycle to cycle, there is an opportunity to qualitatively increase the strength of boxers already in the preparatory period without harming the technical side of sportsmanship. Conclusions. Complex development of strength abilities allows to optimize the process of strength development in boxers aged 17-19 at the stage of sports improvement in the preparatory period of the annual macrocycle.
Efficiency of the method of improving strength abilities of boxers using athletics exercises
Keywords: бокс; силові здібності; кростренінг; легка атлетика; boxing; strength abilities; crosstraining; athletics